The debate on private property in the 21st century: a review of its philosophical foundations - Paredes Gonzalo, Febres (2024)
Given the emergence of new and repeated criticisms of private property today, the tendency to question it is reinforced, even with all the ravages it produced in the last century, as is the case in some Latin American territories and in the East. Naturally, this ideological-political conﬂict has repercussions in Law and in its deepest foundations, that is, in the ﬁeld of the philosophy of law. In view of this, the present research proposes to review the philosophical foundations that trigger the problem, starting from the premise that private property is not an immoral practice. For this purpose, the historical evolution of the concept is reviewed and it is analyzed whether its repercussions are favorable or unfavorable, to then show the economic beneﬁts it brings with it, and to conclude by arguing that its existence is key to peace and growth in any society.